Competition for forest resources: The role of biomass and biofuels in decarbonizing the Swedish industry sector - Braganza, Percy; Pawar, Ritesh (My University, 2021)
This report explores different pathways of technological developments in the steel and cement industries and on how the integration of biofuel and biomass can contribute to decarbonizing the Swedish industrial sector. The study employs a combination of qualitative review and quantitative analytical techniques, including scenarios and stylized models. The results demonstrate how different strategic decisions with regards to production processes, choice of energy carriers and possible implementation of carbon capture, may have significant long-term effects on energy usage and CO2 emissions. Based on the findings, it can be concluded that the available biomass in Sweden is sufficient to meet the needs of the cement and steel industries if alternative paths are chosen but the technical shift will likely result in a significant increase overall electricity demand.